The Rivalry of Rome and Parthia in the Sources from the Augustan Age to Late Antiquity - Overtoom, Nikolaus L. (Anabasis. Studia Classica et Orientalia, 2016)
This article examines the longstanding rivalry of Rome and Parthia, which began as an unintended consequence of Crassus’ decisive defeat at Carrhae in 53 BCE. It synthesizes the accounts and opinions of numerous Graeco-Roman writers from the Augustan Age to late antiquity in order to help illustrate the new and interconnected post-Carrhae world and its legacy. The rivalry of the Romans and Parthians became a primary focus of their foreign policies and drastically expanded their perceptions of the world in which they interacted. Even after the fall of the Parthians to the rebellious Sassanid Persians in the 220s CE, the Romans continued to find their three-century-long rivalry with the Parthians of interest and relevant to the changing world of late antiquity.